Reprezentacije doma in hrepenenja po domu v procesih nacionalizacije slovenske narodnozabavne glasbe - Šabec, Ksenija (Dve domovini, 2023)
The nationalization of music is more intense in those musical genres that the nation recognizes as traditional. Experts, performers, creators, cultural policy, consumers, and mass media play an important role in this context. Home and homeland are dominant markers of national belonging in their representational image. However, in the contemporary context of migration, the notion of home has also acquired new conceptual frameworks. Based on the findings of contemporary home studies in the milieu of migration, the article compares them with its representations in Slovenian folk-pop music, where home, homeland, Slovenia, longing, mountain, Slovenian places, and mother appear as dominant markers of the national.
Keywords: Dom; Domovina; Izseljevanje in priseljevanje; Nacionalizem; Slovenska narodnozabavna glasba